As experiências de desenvolvimento sustentável do Quilombo de Ivaporunduva: um estudo de caso na perspectiva da Agroecologia - Pedroso, Fabio Graf (2008)
This study aim to describe and analyze the main actions directed for the sustainable development of Ivaporunduva`s quilombola community, located at Ribeira Watershed, State of Sao Paulo. Although several local initiatives, this study focused into three main action lines: production, certification and commercialization of organic bananas; banana straw handicraftwork; and conservation, recovery and sustainable use of juçara palm tree. The research was carried through a case study, using different instruments for data collection: documentary analysis, informal interviews and participant observation. The experiments were analyzed by an agroecology perspective, adopting its concepts and principles as theoretical guideline of models and procedures for sustainable rural development. In this direction, it sought to analyze the processes from the three basic dimensions of sustainability, so as to identify and evaluate the main ecological, economic and social results obtained with the interventions. The study was conduced in a narrow relationship with the Ivaporunduva´s Quilombo Association and Instituto Socioambiental (ISA), partner entities responsible for projects implementation in the community. The results demonstrate that the interventions have brought significant contributions from an agroecological perspective, highlighting itself to environmental conservation, socioeconomic development and community s life quality improvement.